Regulation of Neuroinflammation: What Role for the Tumor Necrosis Factor-Like Weak Inducer of Apoptosis/Fn14 Pathway? - Boulamery, Audrey; Desplat-Jégo, Sophie (Frontiers in Immunology, 2017)
Observed in many central nervous system diseases, neuroinflammation (NI) proceeds from peripheral immune cell infiltration into the parenchyma, from cytokine secretion and from oxidative stress. Astrocytes and microglia also get activated and proliferate. NI manifestations and consequences depend on its context and on the acute or chronic aspect of the disease. The tumor necrosis factor-like weak inducer of apoptosis (TWEAK)/Fn14 pathway has been involved in chronic human inflammatory pathologies such as neurodegenerative, autoimmune or malignant diseases. New data now describe its regulatory effects in tissues or fluids from patients with neurological diseases. In this mini-review, we aim to highlight the role of TWEAK/Fn14 in modulating NI in multiple sclerosis, neuropsychiatric systemic lupus, erythematosus, stroke, or glioma. TWEAK/Fn14 can modulate NI by activating canonical and non-canonical NF-κB pathways but also by stimulating MAPK signaling. These downstream activations are associated with (i) inflammatory cytokine, chemokine and adhesion molecule expression or release, involved in NI propagation, (ii) MMP-9 secretion, implicated in blood-brain barrier disruption and tissue remodeling, (iii) astrogliosis and microgliosis and (iv) migration of tumor cells in glioma. In addition, we report several animal and human studies pointing to TWEAK as an attractive therapeutic target.